(untitled) (Research, Society and Development, 2021)
Medical care can prolong life, but health depends on the conditions that cause disease and solid waste and garbage are sources of several health problems. The absence of a more active posture by the State can increase health problems arising from poor management of solid waste and garbage. Studies have indicated problems in waste management in a city in the Amazon context. In this sense, the objective of this article is to identify the causes of the problems of poor management of solid waste and garbage in this city in the Amazon context from the analysis of these works. To this end, a documentary analysis of a set of works from the National Plan for teacher training was used to identify the main bottlenecks regarding waste and garbage management in the city of Alenquer-PA. The results show that the problems of poor waste and garbage management are only a reflection of the political problems faced by municipal management. The problems are linked to the power struggle between political groups in the city that lead to political inaction and degradation of the different services offered to the population. It appears that local contexts and capacities have the power to limit basic services, to boost political, social and environmental problems that put human health at risk.